Distribution and reduction magnitude of HIV-DNA burden in CD4+ T cell subsets depend on art initiation timing. (24th April 2018) - Gantner, Pierre; Barnig, Cindy; Partisani, Marialuisa; Lee, Guinevere Q.; Beck-Wirth, Geneviève; Faller, Jean-Pierre; Martinot, Martin; Mosheni-Zadeh, Mahsa; Cheneau, Christine; Batard, Marie-Laure; Fischer, Patricia; Fuchs, Anne; et al.
Abstract : Objective: The aim of our study was to analyze the dynamics of HIV-DNA levels in CD4 + T-cell subsets in individuals starting successful dolutegravir-based regimens. Design: Twenty-seven individuals with acute infection (AI, n = 8) or chronic infection (CI, n = 5) and patients in virological success (VS, n = 10) or virological failure (VF, n = 4) on antiretroviral therapy (ART) who initiated a dolutegravir-based regimen were enrolled (NCT02557997). Methods: CD4 + T-cells from baseline and week 48 of successful treatment were sorted into effector memory (TEM), transitional memory (TTM), central memory (TCM) and naïve (TN) cell groups for total HIV-DNA measurements by qPCR. Bayesian methods were used to estimate the posterior probability of a HIV-DNA decrease more than 0.25 log copies/10 6 cells at week 48. Results: All patients achieved HIV-RNA suppression at 48 weeks. At baseline and week 48, the highest contributions to the HIV-DNA-infected pool from CD4 + T cells were observed in TTM cells in the AI group (62.4 and 60.2%, respectively), but in TCM cells for the CI, VS and VF groups (54.6 and 59.4%, 58.2 and 62.9%, 62.4 and 67.2%), respectively. HIV-DNA burden declined in all subsets after 48 weeks of treatment in the AI (probability (Pr) > 91%), CI (Pr > 52%) and VF (Pr > 52%) groups, but only in TEM cells in the VS group (Pr = 95%). Conclusion: Our study showed that dolutegravir-based treatment reduced the HIV-DNA cellular burden in individuals from the AI, CI and VF groups, though the reduction levels differed between the patient subgroups. Early treated patients had the highest probability of HIV-DNA reduction. Interestingly, in the aviremic VS group, HIV-DNA reduction was limited to TEM cells. Abstract : Supplemental Digital Content is available in the text